IGSO 위성 가시성 변화에 따른 RNSS 환경에서의 벡터추적루프 기반 수신기 성능분석 - 정희수; 노재희; 홍진석; 지규인; Heesoo Jeong; Jae Hee Noh; Jin Seok Hong; Gyu-In Jee (Journal of Positioning, Navigation, and Timing, 2025)
Global Navigation Satellite System (GNSS) operates with 20 to 40 satellites while Regional Navigation Satellite System (RNSS) is served by approximately 10 satellites. Consequently, the limited number of satellites can adversely affect stand-alone positioning. To overcome this limitation, it is important to track as many satellites as possible for as long as possible. In this study, we introduce a vector tracking loop technique that utilizes strong signals to compensate for weak signals. However, during the vector tracking loop process, there is a possibility that a weak signal may negatively affect other signals. To address this problem, an adaptive covariance matrix was applied to optimize the tracking loop structure based on the residuals between the prediction phase and the actual measurements. For the extended QZSS (consisting of three GEO and four IGSO), we applied a minimum-angle criterion to analyze the visibility in a flat environment. By generating and processing signals under conditions of varying number of visible satellites, we found that the vector tracking loop outperforms the scalar tracking loop by more than 70% in reducing the Distance Root Mean Square (DRMS) when the signal is attenuated due to the decreasing elevation angle of the IGSO satellites.